Favorable Outcome in Coccidioides Endophthalmitis—A Combined Medical and Surgical Treatment Approach. Issue 11 (November 2017) - Ling, Jennifer J.; Bays, Derek J.; Thompson, George R.; Moshiri, Ala; Mannis, Mark J.
Abstract : Purpose: To describe a case of Coccidioides endophthalmitis that resulted in a favorable visual outcome after a combined medical and surgical approach. Methods: A 33-year-old previously healthy woman was referred for evaluation of dyspnea and left-sided vision loss, which began 3 months before, after a trip to Nevada. She was found to have a pulmonary cavitary lesion and fluffy white material in the anterior chamber. An aqueous and vitreous paracentesis grew Coccidioides species. She was managed medically with a total of 7 weekly intravitreal injections of amphotericin B and intravenous liposomal amphotericin B followed by transition to oral posaconazole. Seven months after presentation, to ensure ocular sterilization and to clear the visual axis, she underwent temporary keratoprosthesis implantation, anterior segment reconstruction, removal of a cyclitic membrane and the crystalline lens, pars plana vitrectomy, placement of a pars plana Ahmed drainage device, and penetrating keratoplasty. Results: After surgical intervention and with maintenance posaconazole therapy, the patient had resolution of her dyspnea and improved uncorrected (aphakic) vision with a clear corneal graft, quiet anterior chamber, and normal optic nerve and retina. Conclusions: A combined medical and surgical approach resulted in a favorable visual outcome and avoided the need for enucleation.